Comparison of the Radioactivity Level of Bird’s Eye Chilli in Chemical and Natural Fertilizers - Fatihah Syafinaz Kamarul Zaman (International Journal of Allied Health Sciences, 2025)
Background: Concerns regarding naturally occurring radionuclides in agricultural inputs have increased due to their potential transfer into food crops. This study evaluates the activity concentrations of K-40, Th-232, and Ra-226 in chemical and natural fertilizers and examines their subsequent uptake in Bird’s Eye chilli to assess radiological safety. Methods: Twelve samples comprising chemical fertilizers, natural fertilizers and bird’s eye chilli were collected and analyzed using a High Sensitivity Gamma Spectrometer GDM 10C equipped with WinDAS software. Activity concentrations of the selected radionuclides were quantified, and further assessments of radium equivalent activity (Raeq), absorbed dose rate, and annual effective dose were performed. Data processing and comparative analyses were conducted using Microsoft Excel. Results: All three radionuclides were detected in both fertilizer types. Activity concentrations in fertilizers ranged from 1.3329×10?? to 6.3679×10?? Bq/kg, while bird’s eye chilli samples showed higher values ranging from 3.9453×10?? to 9.7137×10?? Bq/kg. Chemical fertilizers exhibited higher radioactivity indicators, with average Raeq (3.6147 Bq/kg), absorbed dose rate (1.6472 nGy/h), and annual effective dose (0.0202 mSv) compared to natural fertilizers (1.7146 Bq/kg, 0.7941 nGy/h, and 0.0097 mSv, respectively). Correspondingly, chillies grown with chemical fertilizers showed a higher annual ingestion dose of K-40, Th-232, and Ra-226. Conclusion: Although radioactivity levels were higher in samples influenced by chemical fertilizers compared to natural fertilizers, all measured doses remained well below the public exposure limit of 1 mSv/year. Therefore, the bird’s eye chilli samples analyzed in this study are considered radiologically safe for human consumption.